500 The impact on healthcare of reimplantation and long-term mortality after transvenous lead extraction in patients with device related infection. (8th December 2021) - Narducci, Maria Lucia; Ruscio, Eleonora; Nurchis, Mario Cesare; Pascucci, Domenico; Pelargonio, Gemma; Bencardino, Gianluigi; Perna, Francesco; Spera, Francesco; Pinnacchio, Gaetano; Massetti, Massimo; Damiani, Gianfranco; Crea, Filippo
Abstract: Aims: Transvenous lead extraction (TLE) has become a pivotal part of a comprehensive lead management strategy, dealing with a continuously increasing demand. Nonetheless, literature about long-term outcomes and the impact of a new device implantation on survival is still lacking. Given these knowledge gaps, the aim of our study was to analyse reimplantation and both early and long-term mortality in patients undergoing TLE, even in a public health perspective, specifically clarifying concerns about reimplantation. Methods: This prospective, single-centre, observational, real-world registry consecutively enrolled patients (pts) with cardiac implantable electronic device who underwent TLE at our Hospital, from January 2005 to September 2020. The primary endpoint was to analyse major adverse cardiovascular events (MACEs) in both re-implanted (R Group) and non reimplanted (NR Group); secondary end-point was long-term (after discharge) mortality of the whole cohort, in order to investigate long-term mortality predictors. Results: We enrolled high-risk cohort of 451 pts (mean population age 70 ± 12, with lead dwelling time 81.7 ± 201.2 months) at baseline findings: 92% of pts had an evidence of device infection, a generally impaired heart function with mean left ventricular ejection fraction (LVEF) 44 ± 13% and high rates of comorbidities (15% of pts with hypertension+ diabetes mellitus + renal failure). Three-hundred thirteen (72%) pts were reimplanted, using endocardiac leads in 86% and epicardial leads in 14%. Total MACEs rate was higher in R Group versus NR Group (64% versus 28%, P ≤ 0.001, CI 95%, respectively). In particular, rehospitalizations occurred more frequently in reimplanted population (R group 43% versus NR group 13%, P = 0.001, CI 95%). Long-term mortality rate was 34% (150 pts) at a mean follow up of 5.2 years. The leading contributor to long-term mortality was represented by multiple non-communicable chronic diseases (62%), being sepsis responsible for only 4% of long-term mortality, with a clear evidence of reduced infective burden after TLE and complete antibiotic therapy. At multivariate analysis, we found three independent predictors of long-term mortality: advanced age (> 77 years, OR 1.04, CI 1.02–1.06, P < 0.001), renal failure (eGFR<30 mL/min, OR 1.66, CI 1.15–2.39, P = 0.007) and left ventricular dysfunction before TLE (LVEF<45%, OR 1.58, CI 1.08–2.13, P = 0.017). Conclusions: In patients undergoing TLE for infective indications, our study identified the reimplantation group as high risk group for adverse events before discharge. On the other hand, advanced age, renal failure and systolic dysfunction, as independent predictors of long-term mortality, could be evaluated as a predictive score to assess the mortality risk before the procedure of TLE.